Living With COVID-19 Is A Reality Among Dental Fraternity: A Refection - Che Musa, Muhd Firdaus; Sayed Kamar, Syarifah Haizan; Hassan, Yang Rafidah (Deneysel, Biyoteknolojik, Klinik ve Stratejik Sağlık Araştırmaları Derneği, 2021)
This paper aims to deliberately discuss the impact of the COVID-19 pandemic on the dental fraternity, specifically on how dentistry is practiced, and at the same time to rethink the future of dentistry. It is undeniably that the pandemic has affected a country’s economy, and it has negatively influenced people’s behavior in seeking and maintaining their dental health. Concern has been raised on whether it is safe to visit dental facilities. Several guidelines based on the latest evidence provided by local regulatory authorities to educate and ensure the dental practitioners practice strict precautionary and selective case evaluation approaches. Treatments to patients with symptoms of COVID-19 should be delayed and referred to the relevant healthcare providers. This will encourage the public to seek high quality and safe dental care. Nevertheless, the current changes to practice and restrictions on aerosol-generating procedures provide an opportunity to re-orientate dental care towards a less invasive and more preventive approach, expansion of dental workforce roles and responsibilities and working together in a team to tackle and control the pandemic. A radical reform of oral healthcare systems is therefore requiring a bold decision-making from our political and dental industry leaders.